Loss of the Extracellular Matrix Molecule Tenascin-C Leads to Absence of Reactive Gliosis and Promotes Anti-inflammatory Cytokine Expression in an Autoimmune Glaucoma Mouse Model - Wiemann, Susanne; Reinhard, Jacqueline; Reinehr, Sabrina; Cibir, Zülal; Joachim, Stephanie C.; Faissner, Andreas (Frontiers in Immunology, 2020)
Previous studies demonstrated that retinal damage correlates with a massive remodeling of extracellular matrix (ECM) molecules and reactive gliosis. However, the functional significance of the ECM in retinal neurodegeneration is still unknown. In the present study, we used an intraocular pressure (IOP) independent experimental autoimmune glaucoma (EAG) mouse model to examine the role of the ECM glycoprotein tenascin-C (Tnc). Wild type (WT ONA) and Tnc knockout (KO ONA) mice were immunized with an optic nerve antigen (ONA) homogenate and control groups (CO) obtained sodium chloride (WT CO, KO CO). IOP was measured weekly and electroretinographies were recorded at the end of the study. 10 weeks after immunization, we analyzed retinal ganglion cells (RGCs), glial cells and the expression of different cytokines in retina and optic nerve tissue in all four groups. IOP and retinal function was comparable in all groups. Although less severe in KO ONA, WT and KO mice displayed a significant loss of RGCs after immunization. Compared to KO ONA, a significant reduction of βIII-tubulin stained axons and oligodendrocyte markers was noted in the optic nerve of WT ONA. In retinal and optic nerve slices, we found an enhanced GFAP+ staining area of astrocytes in immunized WT. In retinal flat-mounts, a significantly higher number of Iba1+ microglia was found in WT ONA, while a lower number of Iba1+ cells was observed in KO ONA. Furthermore, an increased expression of the glial markers Gfap, Iba1, Nos2 and Cd68 was detected in retinal and optic nerve tissue of WT ONA, whereas comparable levels were observed in KO ONA post immunization. In addition, pro-inflammatory Tnfa expression was upregulated in WT ONA, but downregulated in KO ONA. Vice versa, a significantly increased anti-inflammatory Tgfb expression was measured in KO ONA animals. Collectively, this study revealed that Tnc plays an important role in glial and inflammatory response during retinal neurodegeneration. Our results provide evidence that Tnc is involved in glaucomatous damage by regulating retinal glial activation and cytokine release. Thus, this transgenic EAG mouse model offers for the first time the possibility to investigate IOP-independent glaucomatous damage in direct relation to ECM remodeling.